2014
DOI: 10.3102/0034654314536781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Good Behavior Game on Challenging Behaviors in School Settings

Abstract: Challenging behavior at school remains a concern for teachers and administrators. Thus classroom management practices to prevent challenging behavior are sorely needed. The Good Behavior Game (GBG) has been found to be useful to positively change student behavior. However, previous reviews of the GBG have not quantified effects, have not focused solely on school and classroom behaviors, and have not examined study features that facilitate greater outcomes. Twenty-two peer-reviewed journal articles were reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
104
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(124 citation statements)
references
References 45 publications
13
104
0
4
Order By: Relevance
“…The original version of the GBG included the following components: dividing the class into teams, stating the rules on how students are to behave, delivering hatch marks contingent on rule violations, and delivering prizes to the winning team(s) that stay below a set criterion (Barrish, Saunders, & Wolf, ). Since Barrish et al (), there have been numerous replications of the GBG with students of different ages, conducted in different settings, and across different target behaviors (see Bowman‐Perrott, Burke, Zaini, Zhang, & Vannest, , and Flower, McKenna, Bunuan, Muething, & Vega, for reviews). Despite the well‐documented effectiveness of the GBG, teachers may perceive some components of the GBG as effortful and therefore may be unwilling to implement it.…”
mentioning
confidence: 99%
“…The original version of the GBG included the following components: dividing the class into teams, stating the rules on how students are to behave, delivering hatch marks contingent on rule violations, and delivering prizes to the winning team(s) that stay below a set criterion (Barrish, Saunders, & Wolf, ). Since Barrish et al (), there have been numerous replications of the GBG with students of different ages, conducted in different settings, and across different target behaviors (see Bowman‐Perrott, Burke, Zaini, Zhang, & Vannest, , and Flower, McKenna, Bunuan, Muething, & Vega, for reviews). Despite the well‐documented effectiveness of the GBG, teachers may perceive some components of the GBG as effortful and therefore may be unwilling to implement it.…”
mentioning
confidence: 99%
“…The team with the fewest violations wins the game and gets a small prize. The GBG has proven to be relatively simple, inexpensive, and effective (e.g., Flower, McKenna, Bunuan, Muething, & Vega, 2014; Tingstrom, Sterling‐Turner, & Wilczynski, 2006).…”
mentioning
confidence: 99%
“…articles found that 87% of published, reviewed evaluations yielded moderate to large effect sizes (Flower, McKenna, Bunuan, Muething & Vega (2014). The review also found that clear, operationally defined target behaviors and the use of rewards are associated with greater effects.…”
Section: Development and Evaluationmentioning
confidence: 95%
“…While the study included a measure to ensure fidelity to the intervention procedures, a second, objective coder was unavailable to assess the accuracy of data reporting, due to necessary changes in group scheduling to accommodate student attendance and discipline. While IOA is considered a standard component of research, and was actively sought by the researcher, systematic review of research of the GBG finds that inclusion of treatment fidelity procedures does not appear to impact the efficacy of the study (Flower, McKenna, Bunuan, et al, 2014). Their review of 22 studies of the GBG found that only 8 included measures to assess fidelity of implementation.…”
Section: Limitationsmentioning
confidence: 99%